Pendistribusian Laba Akuntansi Syariah dalam Perspektif Keadilan Ekonomi Islam - Elyanti Rosmanidar; Machfia Win Hidayat (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2021)
This article aims to analyze the perspective of justice in Islamic Economics with a focus on the study of the distribution of profits in accordance with sharia accounting as a media compatible approach in business management and distribution of profits. In accordance with sharia enterprise theory, company profits must be distributed to parties related to the company, both directly (stakeholders and management) and indirectly (muzakki, community and government), so that economic justice can be achieved.